ANALISA BAKTERI TOTAL PADA BUAH PEPAYA (Carica Papaya L.) YANG DI STERIL MENGGUNAKAN METODE AUTOCLAVE - Didik Purwanto; Anton Yuntarso; Christina Destri Wiwis Wijayanti (Jurnal SainHealth, 2021)
Papaya (Carica papaya L.) is a plant that can be used as traditional medicine. All part of a papaya from the roots to the tips of the leaves have high medical value. The disadvantages of papaya is that if the ripe papaya fruit does not last long and rots easily. Total Plate Number is a number that shows the number of mesophyll bacteria or bacteria that live at 15°C - 55°C in every 1 ml or 1 gram of food samples examined. This study aims to determine how long the effect of the durability of papaya fruit that has been sterilized using autoclave and to determine the total number of bacteria in papaya fruit that has been sterilized using autoclave. Results of the study of papaya fruit samples that had been sterilized using autoclave on day 3, the ALT value was 0.67 × 102 CFU/ml, so it can be said to meet the requirements according to SNI (30°C, 72 jam) 1 × 102 colony/g. Day 4 to day 10 the value obtained was 1.17 – 25.16 × 102 CFU/ml where the value did not meet the requirements according to SNI.